Enlisting Students to Transcribe Historical Climate and Weather Data For Research: Building Knowledge Translation Via Classroom-Based Citizen Science - Drew F. Bush; Victoria Slonosky; Geoffrey Pearce; Renee Sieber (The University of Alabama, 2021)
DRAW (Data Rescue: Archives & Weather) is a citizen science project that asks the Canadian public to take part in transcribing millions of meteorological observations recorded between 1871 and 1963 at McGill University's Observatory in Montreal, Quebec, which was demolished in 1963. We examine how classroom-based curricula can integrate citizen science so youth can learn more about their community via engagement with the local history of weather conditions and impacts. Conducted in March 2018, this research examined knowledge translation during a three-week course module through written reflections, classroom video footage, exit interviews, and a final group research assignment. We worked with 21 students-16- to 20-year-olds enrolled in a social science research methods course at Dawson College, a two-year collège d'enseignement général et professionnel (college of general and vocational education) that attracts local students and is a funded part of education in the province of Quebec. We found knowledge translation was facilitated by student engagement with their community's history and appreciation for aiding credible scientific research. Knowledge translation suffered from attempts to include archival records that could be difficult to find, access, and read. Our work showed that citizen science, as a vehicle for community engagement and scientific literacy, requires considerable contextualization, for example, the use of frequently asked questions, tutorials, and blogs for context, and historical context to ensure knowledge translation takes place.